A compact, modular and low-cost Internet of Things (IoT) platform for air quality monitoring in urban areas. (November 2020) - Spandonidis, Christos; Tsantilas, Stefanos; Sedikos, Elias; Galiatsatos, Nektarios; Giannopoulos, Fotios; Papadopoulos, Panagiotis; Demagos, Nikolaos; Reppas, Dimitrios; Giordamlis, Christos
Abstract: The recent emergence of low-cost sensor technologies, measuring various air pollutants, enables the real-time collection of air pollution data, with high spatio-temporal resolution. In our recent study, we developed and deployed low-cost air quality monitoring sensors and distributed them to citizens of Thessaloniki, Greece. The aim of this study was to provide near real-time air pollution measurements that will allow the better representation of the air pollution levels in the greater area of Thessaloniki. In the current work, we present the low-cost adjustable wireless sensor platform that has been developed for air pollution monitoring in urban areas. The platform can take sensor measurements down to one sample per second and is suitable for Big Data analysis applications such as air quality forecasts, weather forecasts and traffic prediction. The paper aims to contribute to the area of low-cost, distributed sensor networks for Environmental Intelligence applications.